Controlling the spin state of diphenylcarbene via halogen bonding: A theoretical study. Issue 15 (1st March 2018) - Ge, Yang; Lu, Yunxiang; Xu, Zhijian; Liu, Honglai
Abstract: Halogen bonding has recently become an effective tool to control the spin state of reactive carbenes. In this work, a series of the complexes of diphenylcarbene (DPC) that has a triplet ground state with several halogen bond donors RX were theoretically studied, and in particular, the influence of the formation of halogen bonding on the spin state of DPC was extensively explored. The spin flip depends on the difference of halogen bond energies between triplet and singlet, that is, when the difference is large enough a spin flip may occur. Furthermore, the variations of the geometries on complexation may induce the potential energy surfaces of different spin states to intersect, thus leading to intersystem crossing. Based on the energy analysis of the minimum energy crossing points (MECPs), the systems with a smaller MECP‐triplet energy barrier go through intersystem crossing more easily. Halogen bonds in the complexes, where a spin flip takes place, exhibit a partially covalent character, while other complexes show conventional behaviors of halogen bonding. According to charge decomposition analysis, the charge transfer from HOMO (DPC) to LUMO (RX) is identified as a prominent stabilizing interaction in the whole complexes. Abstract : The mechanism of switching the spin state of diphenylcarbene via halogen bonding is explored using density functional theory calculations. The difference of halogen bonding energies between the triplet and singlet complexes and the energy barrier for intersystem crossing have a crucial influence on spin flip, that is, the systems with a larger difference and a smaller energy barrier go through intersystem crossing more easily.